Designing thermal energy harvesting devices with natural materials through optimized microstructures. (April 2021) - Ji, Qingxiang; Chen, Xueyan; Liang, Jun; Laude, Vincent; Guenneau, Sébastien; Fang, Guodong; Kadic, Muamer
Highlights: Thermal harvesting devices are designed through optimized microstructures. Two-scale homogenization theory is applied. Optimal Latin hypercube technique combined with a genetic algorithm is implemented. Extremely good thermal-energy harvesting performances are demonstrated. Abstract: Metamaterial thermal energy devices obtained from transformation optics have recently attracted wide attention due to their vast potential in energy storage, thermal harvesting or heat manipulation. However, these devices usually require inhomogeneous and extreme material parameters which are difficult to realize in large-scale applications. Here, we demonstrate a general process to design thermal harvesting devices with available natural materials through optimized composite microstructures. We first design a cross-shaped microstructure and apply two-scale homogenization theory to obtain its effective properties. Optimal Latin hypercube technique, combined with a genetic algorithm, is then implemented on the microstructure to achieve optimized geometrical parameters. The optimized microstructure can accurately approximate the behavior of transformed materials. We design such devices and numerically characterize good thermal energy harvesting performances. To validate the wide application range of our approach, we illustrate other types of microstructures like split rings and rectangles, and show that they mimic well the required constitutive parameters. The approach we propose can be used to design novel thermal harvesting devices available with existing technology, and can also act as a beneficial vehicle to explore other transformation opticcs enabled designs.